Error-prone ZW pairing and no evidence for meiotic sex chromosome inactivation in the chicken germ line. - Silvana Guioli; Robin Lovell-Badge; James M A Turner (PLoS Genetics)
In the male mouse the X and Y chromosomes pair and recombine within the small pseudoautosomal region. Genes located on the unsynapsed segments of the X and Y are transcriptionally silenced at pachytene by Meiotic Sex Chromosome Inactivation (MSCI). The degree to which MSCI is conserved in other vertebrates is currently unclear. In the female chicken the ZW bivalent is thought to undergo a transient phase of full synapsis at pachytene, starting from the homologous ends and spreading through the heterologous regions. It has been proposed that the repair of the ZW DNA double-strand breaks (DSBs) is postponed until diplotene and that the ZW bivalent is subject to MSCI, which is independent of its synaptic status. Here we present a distinct model of meiotic pairing and silencing of the ZW pair during chicken oogenesis. We show that, in most oocytes, DNA DSB foci on the ZW are resolved by the end of pachytene and that the ZW desynapses in broad synchrony with the autosomes. We unexpectedly find that ZW pairing is highly error prone, with many oocytes failing to engage in ZW synapsis and crossover formation. Oocytes with unsynapsed Z and W chromosomes nevertheless progress to the diplotene stage, suggesting that a checkpoint does not operate during pachytene in the chicken germ line. Using a combination of epigenetic profiling and RNA-FISH analysis, we find no evidence for MSCI, associated with neither the asynaptic ZW, as described in mammals, nor the synaptic ZW. The lack of conservation of MSCI in the chicken reopens the debate about the evolution of MSCI and its driving forces.